Management and archiving system for metal detection robot using wireless-based technology and online database registry - Hakim Adil Kadhim; Nabeel Salih Ali; Dheyaa Mohammed Abdulsahib (Institute of Advanced Engineering and Science, 2019)
The tremendous recent involvement of technology in our life generates a lot of advantages and disadvantages. Nevertheless, and to profoundly augment its positive influence, at the expense of the negatives, most technology be deployed to serve humanity and society. Researchers attractive in developing robust and cooperative robotics that capable of solving difficult tasks without any human control. Metal detector robot is one of the robotics principles due to its effectiveness as compared with manually operated and very slow traditional methods. In this article, three main points that are concentrated 1) Design a robot which is vehicle-mounted sensors that capable of carries the sensors of the metal and obstacle; 2) Control and management system wirelessly by a computer-based to command the robot functions by several sets of user’s rules and manage the robot instructions; and 3) Conduct an integrated system that achieving navigated data via metal detector based on online structured query language database registry. Also, discussed a comparison of the previous detector systems and highlights on several merits. The proposed system capable of fully control the robot also, set the robot operator permissions and rules, stored and archived the navigated results and printed reports and stored in an independent database.